1997
DOI: 10.1093/heapol/12.2.166
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Type of Hospital and Health Insurance on Hospital Length of Stay in Irbid, North Jordan

Abstract: The study aimed at examining the effects of type of hospital and health insurance status on hospital length of stay for three identified medical and surgical conditions. Medical records of 520 patients for the year 1991 were reviewed in one public and one private hospital. Comparison of hospital length of stay for the private (n = 185) versus public sector patients (n = 335) was carried out. The effect of presence of health insurance (n = 189) and the lack of it (n = 325) was also studied. It was found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In the advanced statistical analysis, the groups of illiterate people and primary school level and junior high school group were not different from another meaningfully from the statistical point, but the average of all other groups were meaningfully different from another in the statistical aspect. (11), have all been well-adjusted to this result of research. In some other researches, LOS of people living in the city has increased (8,23).…”
Section: Survey On the Length Of Stay For The Patients With Chronic Omentioning
confidence: 82%
See 4 more Smart Citations
“…In the advanced statistical analysis, the groups of illiterate people and primary school level and junior high school group were not different from another meaningfully from the statistical point, but the average of all other groups were meaningfully different from another in the statistical aspect. (11), have all been well-adjusted to this result of research. In some other researches, LOS of people living in the city has increased (8,23).…”
Section: Survey On the Length Of Stay For The Patients With Chronic Omentioning
confidence: 82%
“…In the study on factors affecting diagnosis and treatment in acute rheumatic fever and controllable variableities of these procedures carried out by Turkish Armed Forces in different power forces it has been found that the physicians attitude and behaviour have significant influence on ALOS (14). The type, severity, structure of illnesses were also found to be significant predictors of ALOS in the study of Mawajdeh (11).…”
mentioning
confidence: 83%
See 3 more Smart Citations